Strategi Investasi Saham PT. GoTo Gojek Tokopedia Tbk (GOTO): Analisis Fundamental dan Teknikal Tahun 2025 - Ilham, Mohamad (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
This study aims to evaluate the stock performance of PT GoTo Gojek Tokopedia Tbk (GOTO) using both fundamental and technical analysis approaches, in order to provide investment recommendations for the year 2025. The fundamental analysis reveals that the company is still incurring losses, as indicated by negative financial metrics such as EPS, ROA, and ROE, which reflect ongoing challenges in profitability and operational efficiency. On the other hand, technical analysis utilizing the Relative Strength Index (RSI) indicates a potential price rebound despite high volatility in stock movements. Overall, the study concludes that GOTO stock is not suitable for short-term investment; however, it may hold long-term potential provided the company can overcome its financial challenges and improve its performance.